A jurisprudential approach to human dignity based on the ontological theory and the theory of the autonomy of will. - Tejeda Barbarito, Erman (Revista de Derecho, 2024)
The purpose of this article is to provide an analysis of human dignity based on the jurisprudence of the Supreme Court of Justice of the Argentine Nation. It will be observed that there are at least two theories that attempt to define it, with distinct consequences in their application: the theory of ontological dignity and the theory of phenomenological or ethical dignity. It will become apparent that the effects sought in determining rights vary depending on which conception is adhered to. This differentiation in its use suggests that human dignity emerges as a concept of discretionary application due to its lack of foundation by the judges. To carry out this analysis, a series of judicial rulings related to the health sector will be considered, as they involve fundamental rights that allow for an in-depth examination of the concept in question.
Keywords: human dignity; human rights; philosophical foundations; jurisprudence